Governance challenges and innovations : financial and fiscal governance - Anheier, Helmut K., 1954- (Oxford University Press, 2013)
'Governance Challenges and Innovations' examines the state of governance with a special focus on financial and fiscal governance in the wake of the crises beginning in 2007. Other chapters assess existing governance-related indicators and propose a new framework for applying governance-related information.